2020
DOI: 10.1111/cge.13830
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in patients with microphthalmia, anophthalmia, and coloboma (MAC) from a consanguineous population

Abstract: Next-generation sequencing strategies have resulted in mutation detection rates of 21% to 61% in small cohorts of patients with microphthalmia, anophthalmia and coloboma (MAC), but despite progress in identifying novel causative genes, many patients remain without a genetic diagnosis. We studied a cohort of 19 patients with MAC who were ascertained from a population with high rates of consanguinity. Using single nucleotide polymorphism (SNP) arrays and whole exome sequencing (WES), we identified one pathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, 7 mutations have been reported in theTENM3 gene in 6 unrelated families, 6 of which are ascribed eye anomalies. Our report would be the 7 th MO and coloboma causative mutation in this gene [2], [26], [28]- [31]. You can see the information of these seven mutations in table 2.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To the best of our knowledge, 7 mutations have been reported in theTENM3 gene in 6 unrelated families, 6 of which are ascribed eye anomalies. Our report would be the 7 th MO and coloboma causative mutation in this gene [2], [26], [28]- [31]. You can see the information of these seven mutations in table 2.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Islam et al identified c.1558C>T (a pathogenic homozygous variant) in the TENM3 gene in a patient who was suffering from cataracts, bilateral iris, and chorioretinal colobomas microphthalmia [31].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, seven mutations have been reported in the TENM3 gene in 6 unrelated families, 6 of which are ascribed eye anomalies. Our report would be the 7 th MO and coloboma causative mutation in this gene 2,26,28‐31 . You can see the information of these seven mutations in Table 2.…”
Section: Discussionmentioning
confidence: 85%
“…Our report would be the 7 th MO and coloboma causative mutation in this gene. 2 , 26 , 28 , 29 , 30 , 31 You can see the information of these seven mutations in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation